2020
DOI: 10.47080/jeltl.v3i2.994
|View full text |Cite
|
Sign up to set email alerts
|

To What Extent Does Youtube Contents-Based Language Learning Promote an English Proficiency?

Abstract: The flourishing development of technological software could have been as the necessary reality. The ever-changing technological learning media emergence as the description of digital disruption in educational contexts. Teaching English as a Foreign Language is regarded as a challenging activity, since language teaching is strongly expected to have a quality teaching strategies to improve English proficiency. YouTube is principally designed to increase both aspects of language competency, and personal aspects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
(7 reference statements)
1
5
0
1
Order By: Relevance
“…Flipped Classroom juga mempengaruhi motivasi siswa secara signifikan melalui keinginan dan kesan positif dari pelaksanaan pembelajaran bahasa Indonesia yang dilakukan. Oleh karena itu, inovasi model pembelajaran memberikan kesempatan siswa dan meningkatkan motivasi belajar secara bertahap (Aprianto, 2020).…”
Section: Hasil Dan Pembahasan Penelitianunclassified
“…Flipped Classroom juga mempengaruhi motivasi siswa secara signifikan melalui keinginan dan kesan positif dari pelaksanaan pembelajaran bahasa Indonesia yang dilakukan. Oleh karena itu, inovasi model pembelajaran memberikan kesempatan siswa dan meningkatkan motivasi belajar secara bertahap (Aprianto, 2020).…”
Section: Hasil Dan Pembahasan Penelitianunclassified
“…According to Tafani (2009), language teachers should encourage and employ the use of English-language movies as a teaching tool. Numerous academics have argued that adopting English language films as a method for language competence development offers a lot of advantages (Aprianto, 2020;Khoshniyat & Dowlatabadi, 2014;Li & Wang, 2015;Madhavi et al, 2023). These benefits include raising students' motivation levels, enhancing their oral and written communication abilities, and expanding their cultural understanding, all of which make learning a language more authentic (Kamrozzaman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…YouTube has many positive impacts on the learners; e.g., they participate in classes enthusiastically, engage in social activities, think critically, comprehend the subject matter effectively, and learn in an independent way (Aprianto, 2020). Sakkir, Dollah, & Ahmad (2020) investigated the learners' perspective on the use of YouTube for attaining their English language proficiency at the English Education Department, Universitas Negeri Makassar, Indonesia, and found that this platform helped them in preparing their assignments.…”
Section: Introductionmentioning
confidence: 99%